1993
DOI: 10.1071/pp9930361
|View full text |Cite
|
Sign up to set email alerts
|

Ash, Carbon Isotope Discrimination, and Silicon as Estimators of Transpiration Efficiency in Crested Wheatgrass

Abstract: Breeding and selection for higher transpiration efficiency (W) has been hampered by tedious and costly methodology. Rapid and less costly methods are needed for screening W in plant improvement programmes. We report the relationship of ash, silicon (Si) concentration, and Si uptake to W in crested wheatgrass (Agropyron desertorum [Fischer ex Link] Schultes), an important C3 range grass in western North America. Clones of crested wheatgrass were grown under three water levels in a field rainout shelter and as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 21 publications
6
18
0
Order By: Relevance
“…Phenological stage is well known to influence silica accumulation [48]. The higher leaf SiO 2 content of R. cochinchinensis' is consistent with the hypothesis that silica concentration increases with the plant's age [10,15]. Our study indicates that R. cochinchinensis' increased its SiO 2 concentrations from May to September.…”
Section: Effect Of Season On Foliar Silica Accumulationsupporting
confidence: 78%
See 2 more Smart Citations
“…Phenological stage is well known to influence silica accumulation [48]. The higher leaf SiO 2 content of R. cochinchinensis' is consistent with the hypothesis that silica concentration increases with the plant's age [10,15]. Our study indicates that R. cochinchinensis' increased its SiO 2 concentrations from May to September.…”
Section: Effect Of Season On Foliar Silica Accumulationsupporting
confidence: 78%
“…Alternatively, enhanced silica accumulation might be an inevitable response. It is well known that silica accumulation is correlated to transpiration [15,55]. Tropical leaves with a high photosynthetic capacity may have higher transpiration rates, thus increasing the silica deposition rate.…”
Section: Effect Of Season On Foliar Silica Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence for that correlation was held to be best for dryland grasses (14). On the basis of nonselective, passive uptake of Si, the Si content of plants might serve as a convenient tracer for water uptake (48), but recent evidence lends little support to a directly proportional relationship between water and Si uptake, even for dryland grasses (49)(50)(51). During its passage through the xylem Si has to remain in solution-i.e., it must remain unpolymerized.…”
Section: Silicon In Plantsmentioning
confidence: 99%
“…Foliar N concentration and mineral concentration exhibited significant clonal and/or female and male variations; clonal means of foliar N concentration were significantly related to tree growth; and clonal means of foliar mineral concentration at lower outer canopy were significantly correlated with clonal means of foliar d 13 C at the dry site. Mineral concentration has been shown to be a promising breeding tool for selecting genotypes with contrasting transpiration efficiencies (Masle et al, 1992;Mayland et al, 1993;Araus et al, 1998), and proposed as a surrogate for carbon isotope discrimination owing to its analytical simplicity (Masle et al, 1992;Mayland et al, 1993). Masle et al (1992) reported a positive linear relationship between total mineral concentration of vegetative tissues and either transpiration ratio or carbon isotope discrimination, and a negative relationship between mineral concentration and d 13 C, which were looser for droughted plants or plants fed with nutrient solution of low concentration.…”
Section: Genetic Variation In Canopy Foliar Nutrient Concentrationmentioning
confidence: 98%